A gender perspective as trigger and facilitator of innovation. Issue 2 (3rd June 2014) - Fogelberg Eriksson, Anna
Abstract : Purpose: – The purpose of this paper is to explore whether a gender perspective contributes to or functions as a driving force for innovations in organizations. The following questions are addressed: how can a gender perspective generate innovations and what are the conditions that favour innovations driven by a gender perspective? Design/methodology/approach: – This study builds on a qualitative case study of an upper secondary school in Sweden, which has been showcased as a good example of gender awareness and gender mainstreaming in schools. Semi-structured interviews with representatives of the school were conducted and documents were analysed. Findings: – The gender perspective contributed to innovations by triggering them and supporting the innovative processes, ensuring that the innovations did not stop at essentialist solutions. New ways of performing core processes were developed with the innovative leverage of the gender perspective. The perspective must be actively used and integrated into the core processes if it is to work properly, which was the case in this school. Research limitations/implications: – This study indicates the importance of conducting further studies on innovations in the public sector as well as acknowledging gender in innovation studies, not least because this study focuses on a local case in a specific national context. Practical implications: – This school exemplifies the use of a gender perspective as a driving force for innovations in organizations. The case points to important organizational conditions for innovation and actual gender-aware innovations. Originality/value: – The study expands the understanding of innovation(s) in organizations and elaborates on the gendered dimensions of innovation as both process and product.